Comparative analysis of the inventory process using manual measurements and laser scanning - Piotr Gleń; Karol Krupa (Budownictwo i Architektura, 2019)
Laser scanning allows the acquiring of spatial data about existing objects. It is used as a modern inventory technique, most often in the creation of archival or conservation documentation. It gives the opportunity to obtain a very large amount of spatial data of the facility thus helping to improve operations in the field of conservation but also reduces the margin of error in the inventory and then design documentation. It is useful due to the growing BIM technology, through which three-dimensional models of existing objects of various scales are obtained. This article presents research comparing the traditional measurement method and the modern one with the use of a laser scanner. The research is a compilation of the duration of architectural inventory techniques as well as the accuracy of the measurements made and of the following architectural drawings. The result of the research is a relative percentage ratio showing the acceleration of inventory works with a simple construction object using modern assistive techniques compared to the traditional method.